Integrating actual time usage into the assessment of examination time extensions provided to disabled college engineering students. Issue 7 (2nd October 2020) - Golan, Maya; Singer, Gonen; Rabin, Neta; Kleper, Dvir
Abstract: In this study, we suggest combining the monitoring of actual examination time used with grades in order to assess examination time extensions in terms of access provision and expected outcome. Using naturally-occurring data collected from a large sample ( N  = 2315) of undergraduate engineering students, we argue that extended examination time may be regarded as providing equal access when a disabled student actually utilizes more examination time than a normally achieving student, regardless of the grade obtained. We further argue that extended examination time may be regarded as resulting in the expected outcome when a disabled student either (a) utilizes less or equal examination time and achieve grades that are lower than a normally achieving student, or (b) utilizes more examination time and achieve grades that are equal to a normally achieving student. In our data, equal access was provided in all courses (i.e. disabled students utilized more time than normal achievers), but the expected outcome (i.e. equal grades) was not observed in software and English examinations. The results of this study emphasize the importance of monitoring actual time usage in addition to performance measures when assessing examination time extensions.